Beyond Survival: How Digital Skills, Financial Technology Adaption, And Financial Literacy Shape Business Performance - Ni Komang Ayu Diah Ambalika; Gusti Alit Suputra; Hurul A’ini Sekar Azzahra; Ida Ayu Dipavali Pradnyani (International Journal of Environmental, Sustainability and Social Science, 2026)
Digital and financial capabilities now sit at the heart of how micro, small, and medium enterprises (MSMEs) hold their ground in fast-shifting markets. This study asks which of those capabilities actually move MSME performance. Using the Resource-Based View as its lens, it tests the influence of financial literacy, digital skills, digital transformation strategy, and financial technology (FinTech) adoption on the business performance of Indonesian MSMEs. Questionnaires were completed by 151 MSME owners and managers recruited through purposive sampling, and responses were processed with Partial Least Squares Structural Equation Modeling in SmartPLS. All constructs satisfied validity and reliability criteria, and the structural model accounted for 93% of the variance in business performance (R² = 0.930). Three of the four predictors proved significant. The largest coefficient belonged to digital transformation strategy (β = 0.371), followed by FinTech adoption (β = 0.308) and financial literacy (β = 0.176). Digital skills showed no significant influence, implying that technological competence accomplishes little on its own unless a coherent transformation strategy puts it to work. These findings deepen the discussion on digital entrepreneurship and MSME performance, and show owners, practitioners, and policy makers where capability building pays off if MSMEs are to stay competitive and sustainable